The Effect of Project-Based Learning (PjBL) On Critical Thinking Skills as Seen from Cognitive Styles - Lismayani Lismayani; Kamid Kamid; Yantoro Yantoro (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study investigates thei effect of the Project-Based Learning (PjBL) model on eighth-grade students’ mathematical critical thinking skills, considering their cognitive styles. The research employed a quasi-experimental design with a non-equivalent control group, involving eighth-grade students of SMP Negeri 24 Kerinci in the 2023/2024 academic year. The sample comprised two experimental classes taught with the PjBL model and one control class taught conventionally. Data were collected using the1 Group Embedded Figures Test (GEFT) to identify students’ cognitive styles and an essay test to measure critical thinking skills. Data analysis was conducted through a two-way ANOVA to examine the effects of the learning model and cognitive style, followed by a t-test for further comparison. The results showed that the PjBL model and students’ cognitive styles significantly influenced mathematical critical thinking skills. Field Independent (FI) students scored higher than Field Dependent (FD) students. However, no significant interaction was found between the learning model and cognitive style, indicating that PjBL provides relatively balanced opportunities for all learners. These findings suggest that PjBL can be an effective and inclusive instructional approach to foster students’ critical thinking, and mathematics teachers are encouraged to integrate it into classroom practice.